SENAM DIABETES TERHADAP KADAR GLUKOSA DARAH PENDERITA DIABETES MELITUS TIPE-2 - Arimbi Arimbi; Haeril Haeril; Wahyana Mujari Wahid (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2022)
This study aims to determine the effect of diabetes exercise intervention on blood glucose levels in type-2 diabetes mellitus. by implementing routine exercise activities for 8 weeks and a frequency of 2 times a week. This research method used the one-group pre-posttest design pre-experiment. The instrument used in this study was blood glucose measurement with a digital glucometer. From the results of the study, it was obtained an overview of blood glucose test data before and after the diabetes exercise intervention in type-2 diabetes mellitus patients at the hospital. Pelamonia Makassar, blood glucose test before, obtained an average value of 239.6 mg/dL, with the lowest blood glucose level of 200 mg/dL and the highest 317 mg/dL, while the final test obtained an average blood glucose value of 179.1 mg /dL, with the lowest blood glucose level of 116 mg/dL and the highest blood glucose level of 224 mg/dL. With a significant value of 0.001 (α ≤ 0.005). The conclusion of this study is that there is an effect of diabetic exercise on reducing blood glucose in type-2 diabetes mellitus patients in RS. Pelamonia City of Makassar.